Nurses and Organizational Citizenship Behavior: contribution to the Italian validation of the Podsakoff et al. scale - Zaghini, Francesco; Biagioli, Valentina; Prandi, Cesarina; Fida, Roberta; Sili, Alessandro (La Medicina del Lavoro, 2015)
Background: Workers engaging in Organizational Citizenship Behaviour (OCB) can benefit colleagues, organization and stakeholders. Such behavior is vital to the efficacy of health care organizations as they can have a positive effect on the quality of care and users’ satisfaction. Therefore, it is important to assess such behaviour with a valid and reliable instrument. Objectives: The purpose of this study was to test, from a confirmatory perspective, the dimensionality of the Italian version of the Podsakoff et al. OCB scale in a large sample of nurses, and at the same time to evaluate the differences in nurses’ OCB considering socio-demographic and job characteristics. Methods: The study included 886 nurses from different health organizations in Italy. The psychometric characteristics of the Italian OCB scale were tested through confirmatory factor analysis (CFA). The differences in nurses’ OCB, according to several socio-demographic and job characteristics, were evaluated through a series of correlations and analysis of variance. Results: The CFA of the Italian OCB scale confirmed the hypothesized factor structure, consisting of three dimensions: altruism, civic virtue and conscientiousness. Nurses’ gender and professional training were positively correlated with OCB, while the amount of extra work was negatively correlated. In regard to clinical work settings, palliative care nurses engaged in OCB more than nurses working in other areas. Conclusions: The Italian OCB scale is a valid and reliable instrument. Its use can support all individuals involved in the promotion of workers’ organizational well-being in implementing processes aimed at fostering nurses’ OCB.